Role of β4* Nicotinic Acetylcholine Receptors in the Habenulo–Interpeduncular Pathway in Nicotine Reinforcement in Mice - Harrington, Lauriane (Neuropsychopharmacology, 2016)
Nicotine exerts its psychopharmacological effects by activating the nicotinic acetylcholine receptor (nAChR), composed of alpha and/or beta subunits, giving rise to a diverse population of receptors with a distinct pharmacology. β4-containing (β4*) nAChRs are located almost exclusively in the habenulo–interpeduncular pathway. We examined the role of β4* nAChRs in the medial habenula (MHb) and the interpeduncular nucleus (IPN) in nicotine reinforcement using behavioral, electrophysiological, and molecular techniques in transgenic mice. Nicotine intravenous self-administration (IVSA) was lower in constitutive β4 knockout (KO) mice at all doses tested (7.5, 15, 30, and 60 μg/kg/infusion) compared with wild-type (WT) mice. In vivo microdialysis showed that β4KO mice have higher extracellular dopamine (DA) levels in the nucleus accumbens than in WT mice, and exhibit a differential sensitivity to nicotine-induced DA outflow. Furthermore, electrophysiological recordings in the ventral tegmental area (VTA) demonstrated that DA neurons of β4KO mice are more sensitive to lower doses of nicotine than that of WT mice. Re-expression of β4* nAChRs in IPN neurons fully restored nicotine IVSA, and attenuated the increased sensitivity of VTA DA neurons to nicotine. These findings suggest that β4* nAChRs in the IPN have a role in maintaining nicotine IVSA.